Tax incentives and Malaysian SMEs performance: a mixed method approach / Nadiah Abd Hamid - Abd Hamid, Nadiah (2015)
Governments around the world have implemented several tax policies to strengthen the competitiveness and investment capacities of the small and medium-sized enterprises (SMEs) specifically, those in the manufacturing sector. In Malaysia, the importance of SMEs in industrialization and economy has led the government to extend tax incentives to eligible SMEs. Successful utilization of tax incentives will enable SMEs to reduce the cost of doing business through deductible tax exemptions.Unfortunately, not many SMEs have been successful in utilizing the granted tax incentives. Hence, the goal of this study is to investigate the performance of Malaysia’s SMEs in manufacturing sector which have been granted tax incentives.Specifically, this study identifies the factors leading to the successful utilization of tax incentives from the SMEs owners’/managers’ perspectives, analyses the financial characteristics differences between successful and unsuccessful SMEs’ utilization of tax incentives and determines the relationship between the financial characteristics, age of the company and tax incentives on SMEs performance. Two methodological approaches for data collection were employed; questionnaire survey and financial statements analysis. For the survey, factor analysis was applied to analyze the key factors leading to successful utilization of tax incentives and the analysis was further extended using Logistic Regression. Discriminant analysis was used to differentiate the financial characteristics between successful and unsuccessful SMEs where the tax exempt income account reported in the financial statements stands as proxy in differentiating both categories of SMEs. On the other hand, Multiple Regression analysis was used to determine the relationship between the financial characteristics, age of the company and tax exempt income account on SMEs performance. Three models were developed to test the three groups of samples; small-sized companies, medium-sized companies and pooled sample of both types of companies. The findings showed that the tax incentives given based on profit is a weak policy tool in stimulating SMEs’ investment, thus limiting them from gaining competitive advantage locally or abroad. Most SMEs have been unsuccessful in utilizing the tax incentives because they are not generating profit consistently. The period at which SMEs are awarded with tax incentives is unsuitable since most of them are making losses in the initial stage of operation. Hence, the tax incentives do not improve their financial position. Lack of monitoring from the relevant awarding authority such as MIDA contributes to the ineffectiveness of tax incentives. The performance of SMEs with tax incentives should be monitored and-evaluated continuously to ensure the objectives of providing tax incentives are achieved. In this study, the term foreign SMEs refers to companies which are registered by foreigners in Malaysia and the purpose of including them is solely to distinguish them from the local Malaysian-owned SMEs.The findings of this study send an important signal to the relevant government agencies and the policy makers to formulate appropriate policy on tax incentives for small-sized and medium-sized companies. Treating both types of companies as single entity in granting tax incentives will distort the equitable principles of the present tax system. Thus, it is worthwhile to apply the macro aspect of the Tax Competition Theory in extending tax incentives to SMEs. Finally, there should be some vital policy reforms which take into consideration the size of the companies since, this study proved that size has significant effect in differentiating between successful and unsuccessful small-sized and medium-sized companies